2014
DOI: 10.1016/j.cell.2014.10.050
|View full text |Cite
|
Sign up to set email alerts
|

A Proteome-Scale Map of the Human Interactome Network

Abstract: SUMMARY Just as reference genome sequences revolutionized human genetics, reference maps of interactome networks will be critical to fully understand genotype-phenotype relationships. Here, we describe a systematic map of ~14,000 high-quality human binary protein-protein interactions. At equal quality, this map is ~30% larger than what is available from small-scale studies published in the literature in the last few decades. While currently available information is highly biased and only covers a relatively sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
1,225
3
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 1,290 publications
(1,308 citation statements)
references
References 57 publications
42
1,225
3
14
Order By: Relevance
“…We found that the transeGenes in this hotspot are enriched for platelet degranulation (Table S8). Moreover, analyzing 25 cis-eGenes having binary interactions identified in a systematic screen for protein-protein interactions (PPI), 30 we found that 15 of them are hub genes in the PPI network ( Figure S3, p < 0.001 for randomly selecting 25 proteins in a PPI network), suggesting that cis-eGenes linked to trans-eQTLs play a central regulatory role in critical biological pathways through their mediation effects on trans-eGenes.…”
Section: Figure 2 Mediation Mechanisms Of Eqtlsmentioning
confidence: 96%
“…We found that the transeGenes in this hotspot are enriched for platelet degranulation (Table S8). Moreover, analyzing 25 cis-eGenes having binary interactions identified in a systematic screen for protein-protein interactions (PPI), 30 we found that 15 of them are hub genes in the PPI network ( Figure S3, p < 0.001 for randomly selecting 25 proteins in a PPI network), suggesting that cis-eGenes linked to trans-eQTLs play a central regulatory role in critical biological pathways through their mediation effects on trans-eGenes.…”
Section: Figure 2 Mediation Mechanisms Of Eqtlsmentioning
confidence: 96%
“…In a recent study, approximately two‐thirds of disease‐causing variants were found to impact at least one protein interaction (Sahni et al , 2015). Although only a minority of human protein interactions have been mapped (Rolland et al , 2014), already 40% of human genes have at least one interaction partner detectable by yeast two‐hybrid assay in a recent screen (Rolland et al , 2014). Taking the union of available assays, we estimate that 57% of known disease‐associated genes (Dataset EV2) already have an assay that is potentially amenable to DMS.…”
Section: Resultsmentioning
confidence: 99%
“…Although we focused our attention on mRNA decay, our results suggest that ERG proteins might achieve control of gene expression by orchestrating multiple processes between transcription and decay. In addition, we have recently found 15 TFs among the RBPMS partners in our proteome-scale human interactome (GO: sequence-specific DNA binding) 47 . Therefore, a wide range of TFs and RBPs may actually collaborate in coupling transcriptional and post-transcriptional processes and machineries through the formation of highly versatile functional platforms.…”
Section: Discussionmentioning
confidence: 99%